QUANTUM DYNAMICS OF THE H+D2-]D+HD REACTION - COMPARISON WITH EXPERIMENT - Dmello, M; Manolopoulos, D; Wyatt, R (1991)
The Kohn variational principle for the log-derivative matrix is used to calculate integral cross sections for H + D2 (v = 0, j = 0) to D + HD (v′ = 0,1,2, all j′) at the experimentally accessible collision energies of 0.55 and 1.3 eV. Comparison is made with experimental and theoretical studies in the literature. Product state relative rotational distributions, vibrational branching ratios, and energy partitioning fractions are all in good agreement with the recent experimental results of Rinnen, Kliner, and Zare. Absolute cross sections are compared with the experimental work of Levene et al. and Johnson et al. Our results agree very well with their experiments. It is found that the quasiclassical results of Blais and Truhlar compare well with the present exact quantum mechanical predictions in many respects, however, the product rotational distributions are "hotter" than the quantal ones. © 1991 American Institute of Physics.